Progression of Corynespora Target Spot and Estimation of Yield Losses in Cotton - Prasad, B. M. V. S.; Bhattiprolu, S. L.; Kumar, V. M.; Jayalalitha, K.; Kumar, D. V. S. R. (International Journal of Bio-resource and Stress Management, 2025)
An investigation was conducted during July, 2019–February, 2020 and July, 2020–February, 2021 at Regional Agricultural Research Station, Lam, Guntur, to assess the influence of weather factors on the progression of Corynespora leaf spot in cotton. The study revealed the maximum and minimum temperatures, evening relative humidity and number of rainy days were critical factors. Another independent field experiment conducted to assess the losses due to Corynespora leaf spot by the application of one to five sprays of propiconazole at 0.1% along with control, in randomized block design, with four replications, showed the lowest per cent disease index (7.4 PDI) and the highest yield (3060 kg ha-1) with five sprays. Per cent disease control and yield showed positive correlation whereas PDI showed negative correlation with number of sprays. Yield and avoidable yield loss showed negative correlation with PDI. Regression analysis indicated that every additional spray resulted in reduction of PDI by 4.89 with goodness of fit (R2) of 98%; increase of PDC by 13.50% with R2 of 99% and promotion of yield to 178.80% in pooled analysis data with R2 97%. Regression analysis of PDI as independent and yield, avoidable yield loss as dependent variables registered increase in 1% PDI resulted in the reduction of yield to 35.41 times with R2 of 92%; comparable increase in 1% PDI resulted in the reduction of avoidable yield loss with 1.31% with R2 as 90%. These results suggested timely protection of crop to minimize yield losses and achieve potential yields.